2017
DOI: 10.24959/cphj.17.1419
|View full text |Cite
|
Sign up to set email alerts
|

The effect of propoxazepam on development of thiosemicarbazide-induced GABA-deficient seizures in mice

Abstract: Aim.To study the mechanisms of action for propoxazepam, a new compound with the analgesic action, on the model of thiosemicarbazide-induced GABA-deficient seizures. Matherials and methods. A chemoconvulsive agent was injected subcutaneously (20 mg/kg) 0.5 hours after intraperitoneal introduction of propoxazepam. The number and the time of appearance of different types of convulsions, as well as the relative number of survived animals (for ED 50 calculation) were registered. Results. The first seizure manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The present behavioral and pharmacological study characterized the seizures induced by TSC in rats. Previous studies have shown the occurrence of TSC-induced epileptic discharges in cats (Dunlop et al, 1960), cerebral excitation in dogs (Roa et al, 1964), and seizures in mice (Golovenko et al, 2017). Due to the lack of studies on the rat and the difference in pharmacokinetic and metabolic properties between the rat and these species (Martignoni et al, 2006), it seemed useful to characterize these seizures in the rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present behavioral and pharmacological study characterized the seizures induced by TSC in rats. Previous studies have shown the occurrence of TSC-induced epileptic discharges in cats (Dunlop et al, 1960), cerebral excitation in dogs (Roa et al, 1964), and seizures in mice (Golovenko et al, 2017). Due to the lack of studies on the rat and the difference in pharmacokinetic and metabolic properties between the rat and these species (Martignoni et al, 2006), it seemed useful to characterize these seizures in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…GABAA antagonists have been well studied, while none of the GAD inhibitors have been commonly used in experimental epileptology or in pharmacological screening. Thiosemicarbazide (TSC) is a drug that inhibits GAD (Collins, 1973), lowers GABA levels in the central nervous system (Roa et al, 1964;Sze et al, 1971), and causes seizure discharges in cats (Dunlop et al, 1960), cerebral excitation in dogs (DanteRoa et al, 1964) and convulsions in mice (Golovenko et al, 2017). The effect of TSC, however, has not been characterized behaviorally despite these existing data.…”
Section: Introductionmentioning
confidence: 99%
“…Водночас дія пропоксазепаму не обмежується лише цим. З'ясувалося [18], що на моделі ГАМК-дефіцитних судом, виклика-них тіосемікарбазидом, пропоксазепам продемонстрував досить високу активність і за формою кривої доза-ефект має антагоністичну взаємодію з тіосемікарбазидом. Отримані результати свідчать про можливе посилення дії ключового ферменту синтезу ГАМКглутаматдекарбоксилази (КФ 4.1.1.15).…”
Section: пропоксазепам -новаторський анальгетичний засіб що гальмує гострий та хронічний біль і має полімодальний механізм діїunclassified
“…Similar to gabapentin and pregabalin, which are well-known drugs used in general medical practice in the treatment of neuropathic pain [5], propoxazepam also has an anticonvulsant effect, which explains the analgesic component of the pharmacological spectrum [6][7][8].…”
mentioning
confidence: 99%